Stewardship as an educational process of social learning and change: two case studies conducted in the Western Cape - Walker, Clara Isabella (Rhodes University, Faculty of Education, Department of Education, 2011)
Stewardship in South Africa, as it is being implemented within the framework of the Biodiversity Stewardship Programme (BSP), is an attempt by conservation agencies to engage landowners in the voluntary securing of parcels of biodiverse land, through signing a contract for a certain time period, not to develop the landscape in ways that will impact negatively on the biodiversity of the area in question. The focus of this study is the relationship between biodiversity stewardship and social learning, as I hope to ascertain how stewardship practices are helping to resolve the current problems of biodiversity loss in the Western Cape. The overall aim of this research is to gain an understanding of how, in its capacity as a conservation education process, the Cape Nature Stewardship Programme can foster social learning amongst the landowners involved in its implementation, by leading them to a better understanding of their environmental responsibilities. Data was generated through the use of interviews and informal discussions with participants together with document analysis, such as brochures, pamphlets and presentations. My approach to the analysis of my data was two-phased. In the first phase, I analysed the data generated from the interview process and from reviewing the documents the stewardship officials supplied me with. The second phase involved looking into the results of the two case studies, and formulating analytical statements which were then used to review the case evidence within a social learning perspective, derived from Wals (2007). In constructing an analytical framework for the interpretation of my data, I drew heavily on Wals' (2007) notion of social learning occurring in sequential activities. I used this insight as a lens through which to trace the educational effects of the implementation of the CNSP in the two case study areas.The research highlighted evidence that Stewardship initiatives should be based on the foundation of social learning and invest time and effort in building an environmental knowledge capital amongst the landowners involved. By equipping them with these necessary conservation skills, one creates a 'community of practice' where those individuals adopt a sustainability habitus contributing towards a change and environmental understanding and practises in field.
Keywords: Environmental education -- South Africa -- Western Cape; Conservation of natural resources -- South Africa -- Western Cape; Natural resources -- South Africa -- Western Cape -- Management; Social learning -- South Africa -- Western Cape; Sustainable development -- South Africa -- Western Cape; Cape Nature Stewardship Programme (South Africa); Biodiversity Stewardship Programme (South Africa)